The Values of Character Education in Learning the Kayie Dance - Sari, Nilam Permata; Budiwirman (Universitas Jambi, Indonesia, 2023)
This research used a qualitative with a descriptive approach. Observation and interview were used to collect the data. The data analysis technique in this research described movement motifs, floor patterns, accompaniment, fashion, and make-up, then analyzing the values of character education. The character values ​​in Kayie dance are to teach teenagers to be good all the time, to always be patient, and to fight to survive. Meanwhile, in society, the educational values ​​taught to teenagers through the Kayie dance are tolerance, respect, maintaining good manners, and being responsible for the surrounding environment. Finally, the value of character education is related to national values. By instilling this value, teenagers can have a sense of love for their regional culture. Character formation through learning values ​​in the Kayie dance aims to know and implement these character values ​​into everyday life. The character values in the Kayie dance make a person tough and strong.